Hydrops, fetal pleural effusions and chylothorax in three patients with CBL mutations. (30th October 2014) - Bülow, Luzie; Lissewski, Christina; Bressel, Rainer; Rauch, Anita; Stark, Zornitza; Zenker, Martin; Bartsch, Oliver
<x xml:space="preserve">Abstract</x> Fetal hydrops, fetal pleural effusions, hydrothorax, and chylothorax, may be associated with various genetic disorders, in particular with the Noonan, cardio‐facio‐cutaneous and Costello syndromes. These syndromes, collectively called RASopathies, are caused by mutations in the RAS/MAPK pathway, which is known to play a major role in lymphangiogenesis. Recently, germline mutations in the Casitas B‐cell lymphoma (CBL) gene were reported in 25 patients and of these, 20 had juvenile myelomonocytic leukemia (JMML). The disorder was named "CBL syndrome" or "Noonan syndrome‐like disorder with or without juvenile myelomonocytic leukemia" (NSLL). To date, prenatal abnormalities have not been reported and it is still debated whether the CBL syndrome falls into the category of a RASopathy, or represents a different entity. Here we report on three unrelated patients with CBL mutations manifesting with hydrops fetalis, fetal pleural effusions and/or congenital hydro‐/chylothorax. Our findings further connect the CBL syndrome with the RASopathies. © 2014 Wiley Periodicals, Inc.